Communication Patterns on Addicted Elementary School-Age Children in Playing Free Fire Games - Muhammad Obby Saputra (Lingkar Studi Komunikasi (LISKI), 2023)
Free fire online game is an online game that is currently popular with elementary school age children. This game, which is currently being played by children, has been downloaded more than one million times. This game is a battleground game. Lots of children have been given personal gadgets by their parents. This makes elementary school-aged children lose track of time and tend to be addicted to free fire online games. In addition, since the pandemic, regulations have been implemented for all citizens not to leave their homes to control the spread of the Covid-19 virus. However, because of this, many children are used to using gadgets and are addicted to online games, especially free fire online games. The role of parents is needed in the condition of children who are addicted to free fire online games. Therefore, researchers want to see how communication patterns occur in families in children who are addicted to playing free fire games. Researchers conducted research in North Sangatta District, East Kutai Regency, East Kalimantan because researchers saw many elementary school-age children who had been given personal gadgets by their parents and played free fire online games. This study uses the constructivism paradigm. This study used descriptive qualitative method. There were 4 key informants in this study consisting of 2 parents and 2 children. As for the supporting informants, namely 1 child's playmate and 1 older sibling, and one expert informant who is a family psychologist. Data collection techniques used in the form of observation and in-depth interviews. To increase the validity of the data, researchers used the triangulation method, namely comparing the results between observations and in-depth interviews obtained. In this study, there are two types of family communication patterns, namely protective communication patterns and pluralistic communication patterns. In this study it was found that the liveliness of communicating with children every day is not enough to eliminate online game addiction in children. Parents should be more aware of their children. Care is needed, as well as an understanding of parenting for children. Keywords: Communication Pattern, Online Game, Free Fire, Children